Adverse events of pexidartinib for the treatment of TGCT: a real-world disproportionality analysis using FDA Adverse Event Reporting System database - Lin, Yu; Zheng, Xinlei; Lin, Li; Chen, Maohua (Frontiers in Oncology, 2025)
IntroductionPexidartinib, an oral selective colony-stimulating factor 1 receptor (CSF1R) inhibitor, is the only systemic therapy approved by the U.S. Food and Drug Administration (FDA) for tenosynovial giant cell tumor (TGCT). While clinical trials have defined its initial safety profile, their limited sample sizes and short follow-up restrict the detection of rare or delayed adverse events (AEs), underscoring the need for real-world pharmacovigilance.MethodsUsing the FDA Adverse Event Reporting System (FAERS) database, we conducted a disproportionality analysis to characterize the post-approval safety profile of pexidartinib and identify unlabeled AEs, applying reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) methods.ResultsAmong 7,168,342 FAERS reports, 668 implicated pexidartinib as the primary suspect, with AEs reported across 26 organ systems. Sixty-seven preferred terms met the criteria of all four signal detection methods, including 16 not listed in the FDA-approved label.DiscussionThe overall safety profile was largely consistent with clinical trial findings, while newly detected AEs suggest possible rare or delayed toxicities in broader patient populations. These results highlight the importance of continuous post-marketing surveillance and support the need for prospective studies to clarify causal relationships.